Petroleum microbiology - Ollivier, Bernard, 1957-; Magot, Michel (ASM Press, 2005)
Annotation Petroleum Microbiology is a stateoftheart presentation of the specific microbes that inhabit oil reservoirs, with an emphasis on the ecological significance of anaerobic microorganisms. An intriguing introduction to extremophilic microbes, the book considers the various beneficial and detrimental effects of bacteria and archaea indigenous to the oil field environment. Presenting fundamental and applied biological approaches, the book serves as an invaluable reference source for petroleum engineers, remediation professionals, and field researchers.First providing basic, updated material on the microbial ecology of oil fields, Petroleum Microbiology explores the impacts of microbial activities on the composition of crude oil and on petroleum production, as well as examining bacterial mechanisms involved in the biodegradation of hydrocarbons. The editors provide a compilation of relevant information and coverage of recent developments, incorporating chapters on fermentative, ironreducing, and nitratereducing microorganisms; biodegradation of petroleum in subsurface geological reservoirs; microbial enhancement of oil recovery; petroleum upgrade through the use of biotechnology; and the microbiology of marine oil spill bioremediation.
Keywords: Petroleum -- Microbiology.; elektronické knihy; electronic books